2018
DOI: 10.3329/cmoshmcj.v16i2.37285
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of An Early Intervention Programme on Children with Autism Spectrum Disorders

Abstract: Background: Autism Spectrum Disorders (ASD) is becoming global problem as it is being diagnosed very frequently amongst the non communicable diseases. Lack of socialization, communication skill and behavioural abnormality are the main problem belongs to the disease. Cornerstone of the management is based on early intervention program directed to improve the communication and socialization skill. In Bangladesh different early intervention strategies are implicated adopting from evidence based practices in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Signi cant improvement found in young age group which was concordant with a previous study in Bangladesh which showed signi cant differences in a number of social communication skills (Zaman et al, 2018). A recent study using Applied behavior analysis therapy was stated the importance of combine effect of intervention starting age and the amount of early intervention on the improvement of children (Vietze & Lax, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Signi cant improvement found in young age group which was concordant with a previous study in Bangladesh which showed signi cant differences in a number of social communication skills (Zaman et al, 2018). A recent study using Applied behavior analysis therapy was stated the importance of combine effect of intervention starting age and the amount of early intervention on the improvement of children (Vietze & Lax, 2018).…”
Section: Discussionsupporting
confidence: 87%